Secreted Clever-1 modulates T cell responses and impacts cancer immunotherapy efficacy - Prince, Stuart; Viitala, Miro; Sjoroos, Riikka; Bendes, Abris a.; Rannikko, Jenna H.; Patten, Daniel A.; di Benedetto, Ilaria; Turpin, Rita; Ylitalo, Arno; Tyni, Laura; Figueiredo, Carlos R.; Bostrom, Pia; et al. (Ivyspring International Publisher, 2026)
Rationale: Clever-1 is a multifunctional scavenger receptor that promotes immunosuppressive activity in macrophages, contributing to tumor immune evasion. Its high expression correlates with resistance to immune checkpoint inhibitors, and co-targeting Clever-1 with anti-PD-1 enhances therapeutic efficacy in refractory tumor models. The humanized anti-Clever-1 IgG4 antibody, bexmarilimab, is under clinical investigation for treating solid tumors (NCT03733990) and hematological malignancies (NCT05428969). Methods: To assess the impact of Clever-1 in cancer, we analyzed plasma samples from breast cancer patients (n=139) and bexmarilimab-treated clinical trial participants (n=193) using TRFIA-based ELISA to quantify secreted Clever-1 (sClever-1). A recombinant sClever-1 protein was produced and characterized biophysically. Functional assays, including flow cytometry, Western blotting, T cell activation, and Jurkat reporter systems, were used to assess interactions with T cells. Mechanistic studies involved extracellular vesicle isolation, pulldown assays, and mass spectrometry. Inhibitor studies and patient-derived tumor explants were used to evaluate the immunomodulatory impact of sClever-1 and its effect on anti-PD-1 responses. Results: sClever-1 was significantly enriched in the plasma of cancer patients and reduced following bexmarilimab treatment. Its release was induced by IFN gamma/LPS via serine protease-dependent cleavage. The recombinant sClever-1 bound selectively to activated T cells via mannose-6-phosphate-mediated interaction with IGF2R, impairing TCR signaling and Th1 expansion. sClever-1 was also associated with macrophage-derived extracellular vesicles and contributed to T cell tolerance and reduced anti-PD-1 efficacy. In tumor explants, sClever-1 bound to activated CD4+and CD8+ T cells and increased TGF beta secretion. Conclusions: These findings identify sClever-1 as a previously unrecognized, immunosuppressive mediator in cancer that operates independently of cellular Clever-1 expression. sClever-1 may serve as both a therapeutic target and biomarker to guide immunotherapy strategies.